Magnesium alloy intravascular stent material with nano water repellent layer and bioactive coating and preparation method of magnesium alloy intravascular stent material

By designing the multi-layer structure of nano-water repelling layer and bioactive coating on the magnesium alloy vascular stent material, the problem of rapid degradation of magnesium alloy vascular stent material in the physiological environment is solved, significantly delaying the degradation rate and maintaining good biocompatibility.

CN119656394AActive Publication Date: 2025-03-21INST OF MATERIALS HENAN ACAD OF SCI +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411886420.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Magnesium alloy vascular stent materials rapidly degrade in the physiological environment, leading to the enrichment of magnesium ions, local alkalization and paracorrosion products, which in turn lead to complications such as inflammation, hyperplasia of the endometrium and thrombosis.

Method used

The preparation method of magnesium alloy vascular stent material using nano-water repelling layer and bioactive coating is used. The multi-layer structure design of fluorination treatment, polydopamine deposition, perfluorodecyl thiol nano-water repelling layer and lipoic acid-Cu(II) coating is significantly reduced.

Benefits of technology

It significantly delays the degradation rate of magnesium alloy vascular stent material, extends service time in the body, while maintaining good biocompatibility and improving biological performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656394A_ABST
    Figure CN119656394A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium alloy intravascular stent material with a nano water repellent layer and a bioactive coating and a preparation method of the magnesium alloy intravascular stent material, and belongs to the field of surface treatment of intravascular stent materials. Hydrophobic molecules containing sulfydryl are introduced to the surface of a pretreated magnesium alloy intravascular stent material to construct a nano water-repellent middle layer, the problem that an existing magnesium alloy intravascular stent is high in degradation rate is mainly solved, the surface of the nano water-repellent layer is modified with a bioactive coating, and the biological performance of the magnesium alloy intravascular stent is further improved. The method is mild in reaction condition, low in cost and beneficial to post-treatment. The developed nano water-repellent middle layer has better hydrophobicity and can obviously delay penetration of water molecules in a physiological environment, so that the degradation rate of a magnesium alloy intravascular stent material is reduced, the in-vivo service time is prolonged, and the biocompatibility of the magnesium alloy intravascular stent is not reduced; the method is high in operability and remarkable in effect, and a new method is provided for surface modification of the magnesium alloy intravascular stent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of surface treatment of magnesium alloy vascular stent materials, and in particular relates to a magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating and a preparation method thereof. Background Art

[0002] Cardiovascular disease has become one of the diseases with the highest morbidity and mortality in the world. There are about 330 million cardiovascular disease patients in my country, and more than 3.5 million people die from cardiovascular disease each year, which has become a major public health problem. In recent decades, metal vascular stent implantation has become the main clinical interventional treatment for stenotic cardiovascular disease due to its advantages of less trauma, faster recovery and less economic burden. However, the non-degradable stents currently used in clinical practice will remain in the body permanently after implantation, which will inevitably cause complications such as inflammation, excessive intimal hyperplasia, and late thrombosis. Magnesium alloys have good biocompatibility and biodegradability, and have great application potential in the field of degradable vascular stent materials. They are currently a hot topic in the research of cardiovascular stent materials. However, the rapid degradation of magnesium alloys in physiological environments causes many adverse reactions, such as magnesium ion enrichment, local alkalization and secondary corrosion products, which lead to the loss of radial support of the stent in the early stage, thus leading to implantation failure.

[0003] Surface treatment is an effective strategy to slow down the degradation rate of magnesium alloys. Fluoridation is a technique for preparing a fluoridated film on a magnesium substrate. Sun et al. found that the magnesium fluoride protective layer formed by fluoridation significantly inhibited the degradation rate of magnesium alloy vascular stent materials, but the cell compatibility of the fluoridated layer was poor [Progress in Organic Coatings 187(2024) 108177]. In a previous study, our team induced the formation of a polythioic acid copper precursor solution in an ethanol solution, which was then prepared on the surface of a fluoridated magnesium alloy vascular stent. The corrosion current density of the magnesium fluoride-polythioic acid copper coating sample was 9.16×10 -8 A / cm 2 , with good adhesion (~603 mN) and biocompatibility, and the endothelialization effect is better than that of drug eluting coatings [ZL202211508122.2]. In subsequent follow-up studies, animal implantation experiments showed that magnesium fluoride-copper polylipoic acid coated stents have good anti-proliferation and rapid endothelialization effects. However, magnesium fluoride-copper polylipoic acid coatings still have certain problems. On the one hand, the coated stent needs to undergo a compression and expansion process during implantation, and the adhesion of the coating needs to be further improved; on the other hand, the degradation volume of the coated stent is about 38.5% after 6 months of implantation. Although the magnesium fluoride-copper polylipoic acid coated stent meets the radial support force during revascularization, the degradation rate still needs to be further slowed down to avoid late restenosis of the vessel. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating and a preparation method thereof, which has a low preparation cost, an intermediate layer with good hydrophobicity, can significantly reduce the degradation rate of the magnesium alloy vascular stent material, prolong the service time in the body, and does not reduce the biocompatibility of the magnesium alloy vascular stent, and has good biocompatibility; the surface of the nano water-repellent layer can also be subsequently modified with a lipoic acid-based bioactive coating to further improve the biological properties of the magnesium alloy vascular stent.

[0005] Based on the above purpose, the present invention adopts the following technical solution: A method for preparing a magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating comprises the following steps: (1) Take a magnesium alloy vascular stent material, use sandpaper to grind it until the surface is flat and smooth, rinse it with deionized water and anhydrous ethanol in sequence, dry it, and set it aside; (2) fluoriding the magnesium alloy vascular stent material of step (1) to obtain a sample having a magnesium fluoride layer on the surface; The specific process is as follows: immersing the magnesium alloy vascular stent material of step (1) in a hydrofluoric acid solution with a concentration of 35-40wt%, reacting at room temperature for 12-48 hours, cleaning, and drying to obtain a magnesium fluoride coating sample; (3) depositing polydopamine on the surface of the sample in step (2); The specific process is as follows: prepare a tris(hydroxymethyl)aminomethane aqueous solution with a concentration of 10-20 mmol / L, add hydrochloric acid to adjust the pH to 8.5-9.0, then add dopamine hydrochloride to make the concentration of dopamine hydrochloride 2-4 mg / mL, seal and stir for 20-40 min, soak the sample in step (2) in the above solution for reaction for 12-48 h, shake the table at a speed of 40-100 rpm, and react at a temperature of 20°C-40°C, wash with deionized water, and dry to obtain a polydopamine layer sample; (4) dissolving the thiol-containing hydrophobic molecule in an alcohol solvent at a concentration of 1.0-5.0‰ (V / V) to obtain a hydrophobic molecule solution, placing the magnesium alloy vascular stent material obtained in step (3) in the hydrophobic molecule solution, reacting for 6-24 hours at a temperature of 40°C-60°C, then washing with anhydrous ethanol and drying to obtain the product; (5) dissolving lipoic acid in an organic solvent at a concentration of 0.1 g / mL to 0.5 g / mL, adding an inorganic salt at a molar ratio of lipoic acid to the inorganic salt of 5000 to 50:1, stirring until completely dissolved to obtain a lipoic acid-based precursor solution, which is then prepared on the surface of a vascular stent material containing a nano-water-repellent layer, and dried to obtain a bioactive coating on the surface of the nano-water-repellent layer.

[0006] Preferably, the magnesium alloy vascular stent material in step (1) is ZE21B, WE43, AZ31 or AZ91.

[0007] Preferably, the concentration of hydrochloric acid in step (1) is 0.5-2 mol / L.

[0008] Preferably, the thiol-containing hydrophobic molecule in step (4) is perfluorodecyl mercaptan, perfluorooctyl mercaptan, perfluorohexyl mercaptan, n-octadecyl mercaptan, n-hexadecyl mercaptan, n-tetradecyl mercaptan or n-dodecyl mercaptan.

[0009] Preferably, the inorganic salt in step (5) is zinc chloride, zinc sulfate, ferric chloride, ferric sulfate, copper chloride or copper sulfate.

[0010] Preferably, the organic solvent in step (5) is N,N-dimethylformamide, dichloromethane, isopropanol, anhydrous methanol or anhydrous ethanol.

[0011] Preferably, the lipoic acid-based coating in step (5) is prepared by dip coating, spin coating or spray coating.

[0012] Preferably, the drying in steps (1) to (5) is carried out at 40°C to 60°C for 5 to 30 minutes.

[0013] The magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating is prepared by the preparation method.

[0014] The thickness of the magnesium fluoride layer is 0.8 μm~3.0 μm, the thickness of the polydopamine layer is 0.5 μm~2.0 μm, the thickness of the nano water-repellent layer is 100 nm~150 nm, and the thickness of the bioactive coating is 1.0 μm~6.0 μm.

[0015] The application of the magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating in the preparation of in vivo implants.

[0016] The technical effect directly brought about by the above technical solution is low cost and simple operation. The developed nano water-repellent intermediate layer has good hydrophobicity and can significantly delay the penetration of water molecules in the physiological environment, thereby reducing the degradation rate of the magnesium alloy vascular stent material and prolonging the service time in the body without reducing the biocompatibility of the magnesium alloy vascular stent; the surface of the nano water-repellent layer can also be subsequently modified with a lipoic acid-based bioactive coating to further improve the biological properties of the magnesium alloy vascular stent. The method of the present invention has strong operability and good effect, and provides a new method for the surface coating of magnesium alloy vascular stent materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the preparation of the magnesium fluoride / polydopamine / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(II) coating prepared in Example 1; Figure 2 SEM images of the magnesium fluoride layer prepared in the second step of Example 1, the magnesium fluoride / polydopamine layer prepared in the third step, the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer prepared in the fourth step, and the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(II) coating prepared in the fifth step; Figure 3 EDS data graphs of the magnesium fluoride layer prepared in the second step of Example 1, the magnesium fluoride / polydopamine layer prepared in the third step, the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer prepared in the fourth step, and the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(II) coating prepared in the fifth step; Figure 4 FT-IR images of the magnesium fluoride layer prepared in the second step of Example 1, the magnesium fluoride / polydopamine layer prepared in the third step, the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer prepared in the fourth step, and the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(II) coating prepared in the fifth step; Figure 5 Nanoscratch images of the magnesium fluoride layer prepared in the second step of Example 1, the magnesium fluoride / polydopamine layer prepared in the third step, the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer prepared in the fourth step, and the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(II) coating prepared in the fifth step; Figure 6 The water contact angle diagrams of the magnesium fluoride layer prepared in the second step of Example 1, the magnesium fluoride / polydopamine layer prepared in the third step, the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer prepared in the fourth step, and the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(II) coating prepared in the fifth step; Figure 7 In the figure: (a) is a potentiodynamic polarization curve diagram of the magnesium fluoride layer prepared in the second step of Example 1, the magnesium fluoride / polydopamine layer prepared in the third step, the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer prepared in the fourth step, and the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer / thioctic acid-Cu (Ⅱ) coating prepared in the fifth step; (b) is a potentiodynamic polarization curve diagram of the ZE21B magnesium alloy / polydopamine layer and the ZE21B magnesium alloy / thioctic acid-Cu (Ⅱ) coating; Figure 8It is a graph of endothelial cell survival rates of the magnesium alloy of the first step of Example 1, the magnesium fluoride layer prepared in the second step, the magnesium fluoride / polydopamine layer prepared in the third step, the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer prepared in the fourth step, and the magnesium fluoride / polydopamine layer / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(II) coating prepared in the fifth step; Fig. 9 The water contact angle diagrams of the magnesium fluoride / polydopamine / n-dodecyl mercaptan water-repellent layer prepared in the fourth step of Example 2 and the magnesium fluoride / polydopamine / n-dodecyl mercaptan water-repellent layer / lipoic acid-Fe(III) coating prepared in the fifth step. DETAILED DESCRIPTION

[0018] The technical solution of the present invention is further described below in conjunction with examples, but the protection scope of the present invention is not limited thereto.

[0019] The magnesium alloy vascular stent material used in the present invention can be purchased through the Materials Research Center of Zhengzhou University or commercial channels.

[0020] Embodiment 1: A method for preparing a magnesium alloy vascular stent material with a perfluorodecyl mercaptan nano-water-repellent layer and a lipoic acid-Cu(II) coating (bioactive coating), such as Figure 1 As shown, the following steps are included: The material of the magnesium alloy vascular stent is Mg-2.0Zn-0.5Y-0.5Nd magnesium alloy (brand name ZE21B, the specific preparation process can refer to patent CN201110043303.8).

[0021] Step 1: Pretreatment of magnesium alloy The magnesium alloy was cut into cylinders with a diameter of 10 mm and a thickness of 3 mm. The cylinders were polished with 100-mesh, 400-mesh, 800-mesh, and 1000-mesh sandpapers in sequence until the surface was smooth and flat. The cylinders were then rinsed with deionized water and anhydrous ethanol in sequence, dried at 50 °C for 10 min, and set aside.

[0022] Step 2: Surface fluorination treatment of magnesium alloy The polished ZE21B magnesium alloy sheet was placed in a 24-well plate (with a diameter of about 1.5 cm and a well depth of about 2 cm, which can hold about 3.3 mL of solution); Add 2 mL of 40 wt% hydrofluoric acid solution to the wells containing the magnesium alloy sheets, and place the 24-well plate in a fume hood at room temperature for 12 h; The fluorinated ZE21B magnesium alloy sheet was taken out, rinsed with deionized water and anhydrous ethanol in sequence to remove residual hydrofluoric acid, dried at 50°C for 10 min, and set aside.

[0023] Step 3: Polydopamine deposition treatment A 10 mM tris(hydroxymethylaminomethane) aqueous solution was prepared, and a 0.5 mol / L dilute hydrochloric acid solution was added dropwise to adjust the pH to 8.5 to obtain a tris(hydroxymethylaminomethane)-hydrochloric acid solution; Dissolve dopamine hydrochloride in the above tris(hydroxymethylaminomethane)-hydrochloric acid solution to a concentration of 2.0 mg / mL, seal and stir for 30 min to obtain a dopamine solution; The fluorinated ZE21B magnesium alloy sample was placed in a 24-well plate, 1.5 mL of the above dopamine solution was added to each well, and the plate was fixed on a constant temperature shaker at 60 rpm and deposited at 25°C for 12 h. The polydopamine-treated samples were taken out, rinsed with deionized water and anhydrous ethanol in sequence, dried at 50°C for 10 min, and set aside.

[0024] Step 4: Preparation of perfluorodecyl mercaptan nano-water repellent layer Prepare a 1.5‰ (V / V) perfluorodecyl mercaptan ethanol solution, place the polydopamine coating sample in a 50mL beaker, add 30 mL of the perfluorodecyl mercaptan ethanol solution, react at 60°C for 12 h, wash with ethanol three times, and dry at 50°C for 10 min.

[0025] Step 5: Preparation of Lipoic Acid-Cu(Ⅱ) Coating A 0.15 g / mL lipoic acid solution was prepared, the solvent was anhydrous ethanol, and then copper chloride was added, and the molar ratio of copper chloride to lipoic acid was 1:1000 to obtain a lipoic acid-Cu(Ⅱ) solution; The magnesium alloy material containing the perfluorodecyl mercaptan nano-water-repellent layer was immersed in the above-mentioned thioctic acid-Cu (II) solution for 1 s, taken out, and then placed in an oven and dried at 50° C. for 30 min to obtain the magnesium alloy material.

[0026] The prepared magnesium alloy sample modified with magnesium fluoride / polydopamine / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(II) coating is placed in a sample bag and sealed for later use.

[0027] Preparation of magnesium alloy / polydopamine layer The ZE21B magnesium alloy sample after the first step pretreatment was placed in a 24-well plate, and 1.5 mL of 2.0 mg / mL dopamine solution prepared in the third step of Example 1 was added to each well. The well plate was fixed on a constant temperature shaker with a rotation speed of 60 rpm and deposited at 25°C for 12 h. The polydopamine-treated sample was taken out, rinsed with deionized water and anhydrous ethanol in turn, and dried at 50°C for 10 min.

[0028] Preparation of Magnesium Alloy / Lipoic Acid-Cu(Ⅱ) Coating A 0.15 g / mL lipoic acid solution was prepared, the solvent was anhydrous ethanol, and then copper chloride was added, and the molar ratio of copper chloride to lipoic acid was 1:1000 to obtain a lipoic acid-Cu(Ⅱ) solution; The magnesium alloy sample after the first step pretreatment was immersed in the above-mentioned thioctic acid-Cu (II) solution for 1 s, taken out, and then placed in an oven and dried at 50°C for 30 min.

[0029] The thioctic acid-Cu(II) coating sample with a perfluorodecyl mercaptan water-repellent layer embedded on the surface of the ZE21B magnesium alloy prepared in Example 1 was subjected to scanning electron microscopy (SEM) observation, energy spectrum (EDS) analysis, Fourier transform infrared spectroscopy (FT-IR) analysis, nano scratch test, water contact angle test, AC impedance spectroscopy analysis, and endothelial cell AO / EB test. The preparation process is as follows Figure 1 The experimental results are shown in Figure 2-Figure 8 shown.

[0030] Figure 1 This is a diagram of the preparation mechanism of the magnesium fluoride / polydopamine / perfluorodecyl mercaptan water-repellent layer / thioctic acid-Cu (II) coating prepared in Example 1. Perfluorodecyl mercaptan can be grafted onto the surface of polydopamine molecules by Michael addition to form a nano water-repellent layer, and then the thioctic acid-Cu (II) coating is prepared by the immersion and pulling method.

[0031] Figure 2 The SEM images of each layer prepared in Example 1 are shown below. Gold spraying is required before observing the morphology. Figure 2 It can be seen that the surface of the magnesium fluoride coating sample is flat and smooth. After polydopamine treatment, the surface shows a dense nano-scale particle morphology. After the surface is grafted with perfluorodecyl mercaptan, it can be observed that the morphology of the perfluorodecyl mercaptan water-repellent layer is basically similar to that of the polydopamine coating sample. The surface nano-water-repellent layer is very thin and the morphology of the polydopamine coating is not changed. After coating with lipoic acid-Cu (Ⅱ) coating, the surface morphology of the magnesium alloy vascular stent material is uniform.

[0032] Figure 3 The EDS data of each layer prepared in Example 1. The elemental composition of the magnesium fluoride coating sample is mainly Mg and F elements, corresponding to magnesium fluoride. After the polydopamine layer is deposited, the main elements are C, N and O elements. After the surface is grafted with perfluorodecyl mercaptan, the proportion of F and C elements increases significantly, indicating that the perfluorodecyl mercaptan molecules are successfully fixed to the surface of the polydopamine layer. The elemental composition of the lipoic acid-Cu (Ⅱ) coating is mainly S, O and C elements. Due to the low content of Cu element, the presence of Cu element was not detected.

[0033] Figure 4 FT-IR spectra of each layer prepared in Example 1. Figure 4No chemical bonds were detected on the surface of the magnesium fluoride layer sample. After the polydopamine layer was deposited, a chemical bond was detected at 1628 cm -1 and 1410 cm -1 The absorption peak at 1490 cm-1 is attributed to the stretching vibration peak of the C=C bond in the aromatic ring. -1 The peak at 1100-1300 cm corresponds to the shear vibration peak of the NH bond in the polydopamine molecule. -1 The lipoic acid-Cu(Ⅱ) coating showed some obvious absorption peaks in the range of 1706 cm-1, which was attributed to the vibration of the CF bond in the perfluorodecyl mercaptan molecule. -1 ), which is due to the coordination of a part of -COOH with Cu(Ⅱ) to enhance the C=O stretching, 1615 cm -1 The peak at confirms the formation of a coordination bond between Cu (II) and -COOH.

[0034] Figure 5 The nano scratch test of each layer prepared in Example 1 was performed at a constant moving rate (2 mm / min) by increasing the linear load to 5 N at a loading rate of 5 N / min until the scratch distance reached 2 mm. Figure 5 As shown, it can be observed that the critical load of the perfluorodecyl mercaptan water-repellent layer sample is 570 mN, indicating good adhesion. After further modification, the adhesion of the lipoic acid-Cu(Ⅱ) coating reaches 860 mN, which is attributed to the fact that the perfluorodecyl mercaptan water-repellent layer can provide abundant F elements, which can improve the adhesion of the outer layer of lipoic acid-Cu(Ⅱ) coating by forming tight hydrogen bonds with -COOH, which is significantly better than the adhesion of the previously reported magnesium fluoride-polythioic acid copper coating sample (~603 mN) [ZL202211508122.2]. In addition, the nanoscratch test can also reflect the thickness of the coating to a certain extent. It can be found that the thickness of the magnesium fluoride layer, polydopamine layer, perfluorodecyl mercaptan water-repellent layer and lipoic acid-Cu(Ⅱ) coating are approximately 910 nm, 740 nm, 130 nm and 5360 nm, respectively.

[0035] Figure 6The water contact angle experiment of each layer prepared in Example 1. The water contact angle of the magnesium fluoride layer sample is 10.3°, which is due to the presence of the dense and hydrophilic fluorinated layer, which significantly improves the hydrophilicity of the sample. The hydrophilicity of the polydopamine layer surface decreases, and its contact angle increases to 57.7°. After the perfluorodecyl mercaptan is fixed on the surface, the water contact angle of the nano water-repellent layer is 90.2°, which significantly delays the diffusion and penetration of water molecules. The lipoic acid-Cu (Ⅱ) coating is further modified, and the surface contact angle drops to 84.8°. The surface of the biomaterial with moderate hydrophilicity can promote cell growth and improve biocompatibility.

[0036] The electrochemical corrosion behavior of magnesium fluoride / polydopamine / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(Ⅱ) coating samples was studied using an electrochemical workstation. The specific test steps are as follows: the electrochemical workstation was used to perform relevant electrochemical tests, the electrolyte was Hank's balanced salt solution, and the temperature was 37 ℃. All electrochemical measurements were performed in a traditional three-electrode system, in which a platinum sheet was used as a counter electrode, a saturated calomel electrode was used as a reference electrode, and an exposed area of ​​0.78 cm 2 The sample was used as the working electrode. The sample was immersed in Hanks' solution and allowed to stand for 1200 s to allow the open circuit potential to reach a stable state. −1 The potentiodynamic polarization curve of the sample from -2.0 V to 0.0 V was recorded at a constant scan rate, and the corresponding corrosion current density was obtained by Tafel extrapolation. Generally speaking, the lower the corrosion current density, the slower the degradation rate. Figure 7 The potentiodynamic polarization curves of each sample are shown. The corrosion current density of the magnesium fluoride / polydopamine / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(Ⅱ) coating is 2.56 × 10 -8 A / cm 2 , indicating a lower degradation rate, significantly delaying the diffusion and penetration of water molecules. The degradation rate is significantly lower than that of previous studies: the corrosion current density of the magnesium fluoride-polythioic acid copper coating sample is 9.16×10 -8 A / cm 2 [ZL202211508122.2]. In addition, compared with ZE21B magnesium alloy / polydopamine layer (6.28×10 -6 A / cm 2 ) and ZE21B magnesium alloy / lipoic acid-Cu(Ⅱ) coating (4.20 ×10 -5 A / cm 2 ), the corrosion current density of the current magnesium fluoride / polydopamine / perfluorodecyl mercaptan water-repellent layer / lipoic acid-Cu(Ⅱ) coating system is about 2 to 3 orders of magnitude lower.

[0037] Endothelial cells were cultured at 4 × 103 The concentration of cells / hole was inoculated on the bottom of the adhered 24-well plate, and 400 μL of endothelial cell culture medium was added to each well and placed in a constant temperature incubator at 37°C and 5% CO2 for 24 h. Then the waste liquid was removed, and 200 μL of culture medium and sample extract were added to each well at a ratio of 1:1, and 20 μL of fetal bovine serum and 2 μL of penicillin-streptomycin solution were added. This step was repeated every 24 h to replace fresh culture medium. 5 µL of acridine orange (AO) and ethidium bromide (EB) stains were added to the sample in turn, and stained for 5 min in the dark. Observe and take pictures under an inverted fluorescence microscope. Five pictures were selected for each group of samples, and the number of living cells and apoptotic cells in each picture was calculated, and the survival rate of endothelial cells was calculated according to formula 1: Survival rate (%) = surviving cells / (surviving cells + apoptotic cells) × 100% (1) like Figure 8 As shown in the figure, during the entire culture period, the survival rate of endothelial cells in the ZE21B magnesium alloy sample group was the lowest, 93.8±0.87% (1 d) and 94.5±1.98% (3 d), indicating that magnesium alloy promotes the apoptosis of endothelial cells. The survival rate of endothelial cells in the magnesium fluoride layer sample group increased to 95.5±0.49% (1 d) and 97.3±0.16% (3 d), but it still caused the apoptosis of endothelial cells. After the polydopamine layer was modified, the survival rate of endothelial cells in the sample group was significantly improved to 97.7±0.44% (1 d) and 98.1±0.38% (3 d), which significantly promoted the survival of endothelial cells. After the surface was modified with perfluorodecyl mercaptan nano-water-repellent layer, the survival rate of endothelial cells was 97.8 ± 0.28% (1 d) and 98.1 ± 0.60% (3 d), and the biocompatibility of the polydopamine layer was not reduced. For the lipoic acid-Cu(Ⅱ) coating sample, without adding NO donor component, the survival rate of endothelial cells was 98.08 ± 0.99% (1 d) and 99.14 ± 0.02% (3 d), which had good endothelial cell compatibility. After the introduction of NO donor, the survival rate of endothelial cells in the lipoic acid-Cu(Ⅱ) coating sample was further increased to 99.09 ± 0.14% (1 d) and 99.83 ± 0.01% (3 d), respectively, which significantly promoted the proliferation of endothelial cells. Embodiment 2: A method for preparing a magnesium alloy vascular stent material with a n-dodecyl mercaptan nano water-repellent layer and a thioctic acid-Fe(II) coating (bioactive coating), comprising the following steps: The material of magnesium alloy vascular stent is ZE21B magnesium alloy.

[0038] Step 1: Pretreatment of magnesium alloy The magnesium alloy was cut into cylinders with a diameter of 10 mm and a thickness of 3 mm. The cylinders were polished with 100-mesh, 400-mesh, 800-mesh, and 1000-mesh sandpapers in sequence until the surface was smooth and flat. The cylinders were then rinsed with deionized water and anhydrous ethanol in sequence, dried at 50 °C for 10 min, and set aside.

[0039] Step 2: Surface fluorination treatment of magnesium alloy The polished ZE21B magnesium alloy sheet was placed in a 24-well plate (with a diameter of about 1.5 cm and a well depth of about 2 cm, which can hold about 3.3 mL of solution); Add 2 mL of 40 wt% hydrofluoric acid solution to the wells containing the magnesium alloy sheets, and place the 24-well plate in a fume hood at room temperature for 24 h; The fluorinated ZE21B magnesium alloy sheet was taken out, rinsed with deionized water and anhydrous ethanol in sequence to remove residual hydrofluoric acid, dried at 50°C for 10 min, and set aside.

[0040] Step 3: Polydopamine deposition treatment Prepare a 20 mM tris(hydroxymethyl)aminomethane aqueous solution, and add 0.5 mol / L dilute hydrochloric acid solution dropwise to adjust the pH to 8.5; Dissolve dopamine hydrochloride in the above-mentioned tris(hydroxymethylaminomethane)-hydrochloric acid solution to a concentration of 3.0 mg / mL, seal and stir for 30 min to obtain a dopamine solution; The fluorinated ZE21B magnesium alloy sample was placed in a 24-well plate, 1.5 mL of the above dopamine solution was added to each well, and the plate was fixed on a constant temperature shaker at 80 rpm and deposited at 30 °C for 24 h; The polydopamine-treated samples were taken out, rinsed with deionized water and anhydrous ethanol in sequence, dried at 50°C for 10 min, and set aside.

[0041] Step 4: Preparation of n-dodecyl mercaptan nano-water repellent layer Prepare a 5.0‰ (V / V) n-dodecyl mercaptan ethanol solution, place the polydopamine sample in a 50 mL beaker, add 30 mL of n-dodecyl mercaptan solution, react at 40°C for 18 h, wash with ethanol three times, and dry at 50°C for 10 min.

[0042] Step 5: Preparation of Lipoic Acid-Fe(III) Coating A 0.3 g / mL lipoic acid solution was prepared using anhydrous ethanol as the solvent, followed by the addition of ferric chloride, with the molar ratio of ferric chloride to lipoic acid being 1:500; The magnesium alloy material containing the perfluorodecyl mercaptan nano-water-repellent layer was immersed in the above solution for 5 s, taken out, and then placed in an oven and dried at 50° C. for 30 min to obtain the material.

[0043] The prepared magnesium alloy vascular stent material modified with magnesium fluoride / polydopamine / n-dodecyl mercaptan water-repellent layer / lipoic acid-Fe(III) coating is placed in a sample bag and sealed for later use.

[0044] The ZE21B magnesium alloy sample with a n-dodecyl mercaptan water-repellent layer on the surface prepared in Example 2 was tested for water contact angle. The experimental results are as follows: Fig. 9 shown.

[0045] Fig. 9 This is the water contact angle experiment of magnesium fluoride / polydopamine / n-dodecyl mercaptan water-repellent layer / lipoic acid-Fe(III) coating prepared in Example 2. After n-dodecyl mercaptan was fixed on the surface, the water contact angle of the nano water-repellent layer was 91.6°, which has good water repellency. After modifying the lipoic acid-Fe(III) coating, the surface contact angle dropped to 89.8°.

[0046] The above description is only a partial implementation mode of the present invention. For ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the principle of the present invention. These improvements and substitutions should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating, characterized in that: The following steps are involved: (1) Take a magnesium alloy vascular stent material, use sandpaper to grind it until the surface is flat and smooth, and then clean it, dry it, and set it aside; (2) fluoriding the magnesium alloy vascular stent material of step (1) to obtain a sample having a magnesium fluoride layer on the surface; (3) depositing polydopamine on the surface of the sample in step (2); (4) dissolving the thiol-containing hydrophobic molecule in anhydrous ethanol at a concentration of 1.0-5.0‰ (V / V) to obtain a hydrophobic molecule solution, placing the magnesium alloy vascular stent material obtained in step (3) in the hydrophobic molecule solution, reacting for 6-24 h at a temperature of 40°C-60°C, then washing with anhydrous ethanol and drying to obtain the product; (5) dissolving lipoic acid in an organic solvent at a concentration of 0.1 g / mL to 0.5 g / mL, adding an inorganic salt at a molar ratio of lipoic acid to the inorganic salt of 5000 to 50:1, stirring until completely dissolved to obtain a lipoic acid-based precursor solution, which is then prepared on the surface of a vascular stent material containing a nano-water-repellent layer, and dried to obtain a bioactive coating on the surface of the nano-water-repellent layer.

2. The preparation method according to claim 1, characterized in that The magnesium alloy vascular stent material described in step (1) is ZE21B, WE43, AZ31 or AZ91.

3. The preparation method according to claim 1, characterized in that: The hydrophobic molecule containing a thiol group in step (4) is perfluorodecyl mercaptan, perfluorooctyl mercaptan, perfluorohexyl mercaptan, n-octadecyl mercaptan, n-hexadecyl mercaptan, n-tetradecyl mercaptan or n-dodecyl mercaptan.

4. The preparation method according to claim 1, characterized in that: The inorganic salt described in step (5) is zinc chloride, ferric chloride, ferric sulfate, cupric chloride or cupric sulfate.

5. The preparation method according to claim 1, characterized in that: The organic solvent described in step (5) is N,N-dimethylformamide, dichloromethane, isopropanol, anhydrous methanol or anhydrous ethanol.

6. The preparation method according to claim 1, characterized in that: The lipoic acid-based coating in step (5) is prepared by dip coating, spin coating or spray coating.

7. A magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating obtained by the preparation method according to any one of claims 1 to 6.

8. The magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating according to claim 7, characterized in that: The thickness of the magnesium fluoride layer is 0.8 μm~3.0 μm, the thickness of the polydopamine layer is 0.5 μm~2.0 μm, the thickness of the nano water-repellent layer is 100 nm~150 nm, and the thickness of the bioactive coating is 1.0 μm~6.0 μm.

9. Use of the magnesium alloy vascular stent material with a nano water-repellent layer and a bioactive coating as claimed in claim 7 or 8 in the preparation of an in vivo implant.

Citation Information

Patent Citations

  • Mg-Zn-Y-Nd alloy for novel biodegradable vascular stents and preparation method thereof

    CN102220529B

  • Preparation method for corrosion-resistant hydrophobic film on metal surface

    CN106367753A

  • Hydrophobic magnetic porous material and preparation and application thereof

    CN113351178A

  • Novel degradable magnesium alloy intravascular stent and preparation method thereof

    CN114904052A

  • Method for preparing copper polylipoate coating on surface of cardiovascular and cerebrovascular stent material and cardiovascular and cerebrovascular stent material containing coating

    CN115581808A